ABOUT THE ACCORDANCE BETWEEN THE CANONICAL VEKUA DIFFERENTIAL EQUATION AND THE GENERALIZED HOMOGENEOUS DIFFERENTIAL EQUATION - Brsakoska, Slagjana (Matematichki Bilten, 2016)
In the paper two equations, the canonical Vekua differential equation and the generalized homogeneous differential equation, are considered. The main result is the theorem with the condition for the accordance between this two equations.